Shelley’s Compassion for the Monster and Hatred for Victor in Frankenstein - Lamichhane, Hari Krishna (Rural Development Journal, 2019)
This paper seeks to study certain affects that Mary Shelley is trying to evoke in Frankenstein for the Monster and against Victor Frankenstein along with other characters in the novel. Though the Monster is taken as the villain in the novel, the research tries to justify him as the good character claiming that whatever he does is just because of the misbehavior his creator, Victor Frankenstein along with other characters in the novel does upon him. The paper applies the theory of affect to study the contrasting representations of the Monster and Victor Frankenstein in the novel. The significance of this approach is the clarity of the cultural politics of the representation and the exposing of Shelley’s love for the Monster. But the question arises, what opposing affects Shelley evokes against the two characters. The conflicting affects, the paper argues, are those of love and respect for the Monster and hatred and disrespect for Victor Frankenstein. The objective of this paper is to justify that every creature in the world has the right to life and that everyone needs love and compassion from others to be happy otherwise one may turn to be destructive like the Monster himself. The particular theory of the affects of love and hatred comes from Sara Ahmed’s The Cultural Politics of Emotion (2003) and the affect of compassion from Ruth Leys’ From Guilt to Shame (2007). Finally, the paper asserts that in the novel, Frankenstein, Shelley claims that every creature in the world has the right to life and that everyone needs love and compassion from others to be happy otherwise one may turn to be destructive like the Monster.